2016
DOI: 10.7287/peerj.preprints.1631v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of biochar and chemical fertilizer to enhance quality of soil and wheat crop (Triticum aestivum L.)

Abstract: 21

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Our results demonstrated that IPNS treatments, especially biochar (PMB) and compost (OF)-based IPNS, significantly elevated MBC in both soils and MBN in charland soil. This is consistent with other research (Zhang et al, 2014b;Chaudhry et al, 2016;Liu et al, 2021). MBC and MBN increased by 8.8-50% and 20-180%, respectively, which was comparable with the recent work by Al-Suhaibani et al ( 2020) who observed 20.0-47.5% and 32.2-65.2% increases in MBC and MBN, respectively, as a result of IPNS treatments.…”
Section: Effect Of Ipns On Microbial Biomass Carbon and Nitrogensupporting
confidence: 93%
“…Our results demonstrated that IPNS treatments, especially biochar (PMB) and compost (OF)-based IPNS, significantly elevated MBC in both soils and MBN in charland soil. This is consistent with other research (Zhang et al, 2014b;Chaudhry et al, 2016;Liu et al, 2021). MBC and MBN increased by 8.8-50% and 20-180%, respectively, which was comparable with the recent work by Al-Suhaibani et al ( 2020) who observed 20.0-47.5% and 32.2-65.2% increases in MBC and MBN, respectively, as a result of IPNS treatments.…”
Section: Effect Of Ipns On Microbial Biomass Carbon and Nitrogensupporting
confidence: 93%
“…The increase in plant growth parameters, including plant height and fresh biomass weight, can also be explained by the beneficial properties of biochar. Biochar amendments can increase soil nutrient levels, such as nitrogen (N), phosphorus (P), and potassium (K), which are essential for plant growth. , This can improve soil fertility and a more favorable plant growing environment. Additionally, the porous structure of biochar can improve soil water holding capacity and aeration, which can benefit plant growth and development. …”
Section: Discussionmentioning
confidence: 99%